Induction of δ-Aminolevulinic Acid Synthetase in Chick Embryo Liver Cells in Culture - Sassa, Shigeru (1970)
δ-Aminolevulinic acid synthetase is induced in chick embryo liver culture by the natural steroid, etiocholanolone, and by the foreign chemical, 3,5-dicarbethoxy-1,4-dihydrocollidine at the level of transcription. Alternatively, inducing chemicals such as allylisopropylacetamide and γ-hexachloro-cyclohexane act primarily at the level of translation. Hemin (K(i) = 5 μM) inhibits the induction at the level of translation. In liver cell culture, the half-life of δ-aminolevulinic acid synthetase is 3 hr, that of mRNA about 5 hr.